PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK DALAM PELANGGARAN LALULINTAS YANG MENGAKIBATKAN KEMATIAN (STUDI DI POLRES TAPANULI TENGAH) - Jayasa Putra Rajagukguk; Taufik; Azwir Agus (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines criminal liability for minors involved in fatal traffic accidents, analyzes the sanctions and legal application imposed on child offenders, and identifies obstacles and solutions in resolving such cases. The research employs a normative juridical method with a descriptive-analytical approach, relying on library research through secondary data, including primary, secondary, and tertiary legal materials. Qualitative data analysis is applied by interpreting statutory regulations and relevant legal doctrines to address the research problems. The findings indicate that criminal liability for children who cause death in traffic accidents is determined based on age, in accordance with the Juvenile Criminal Justice System under Law No. 11 of 2012. Sanctions are imposed with consideration of the child’s age, particularly for those over 14 years old. In the case occurring in Tapanuli Tengah, the matter was resolved amicably through restorative settlement between the families involved.